Type-2 Fuzzy Granular Models - Sanchez, Mauricio A.; Castillo, Oscar; Castro, Juan R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this book, a series of granular algorithms are proposed. A nature inspired granular algorithm based on Newtonian gravitational forces is proposed. A series of methods for the formation of higher-type information granules represented by Interval Type-2 Fuzzy Sets are also shown, via multiple approaches, such as Coefficient of Variation, principle of justifiable granularity, uncertainty-based information concept, and numerical evidence based. And a fuzzy granular application comparison is given as to demonstrate the differences in how uncertainty affects the performance of fuzzy information granules.
Introduction -- Background and Theory -- Advances in Granular Computing -- Conclusions. .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence